2015
DOI: 10.2214/ajr.14.13489
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility Study of 3-T DWI of the Prostate: Readout-Segmented Versus Single-Shot Echo-Planar Imaging

Abstract: G e nit ou r i n a r y I m ag i ng • O r ig i n a l Re s e a rc h AJR 2015; 205:70-76 0361-803X/15/2051-70 OBJECTIVE. The purpose of this prospective study was to assess the clinical utility of generalized autocalibrating partial parallel acquisition (GRAPPA)-accelerated readoutsegmented echo-planar imaging (rs-EPI) DWI and compare it with standard single-shot EPI ( ss-EPI) DWI in visualization of the prostate during 3-T MRI.SUBJECTS AND METHODS. One hundred sixteen consecutively registered patients (mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 31 publications
1
35
1
Order By: Relevance
“…For reasons of comparability, we adjusted the acquisition parameters of DW‐EPI SMS to the DW‐EPI SS standard and did not assess the potential for acquiring higher spatial resolution, because current DWI sequences with special focus for improving image resolution rely on multishot readout segmented EPI techniques. Several studies have demonstrated the feasibility of this approach for a significant reduction of distortion and susceptibility artifacts; however, at the cost of lengthening the total scan time . To benefit from both accelerated acquisition speed and high spatial resolution, a combination of the SMS‐technique and readout segmented DW‐EPI sequences appears worthwhile to further improve DWI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For reasons of comparability, we adjusted the acquisition parameters of DW‐EPI SMS to the DW‐EPI SS standard and did not assess the potential for acquiring higher spatial resolution, because current DWI sequences with special focus for improving image resolution rely on multishot readout segmented EPI techniques. Several studies have demonstrated the feasibility of this approach for a significant reduction of distortion and susceptibility artifacts; however, at the cost of lengthening the total scan time . To benefit from both accelerated acquisition speed and high spatial resolution, a combination of the SMS‐technique and readout segmented DW‐EPI sequences appears worthwhile to further improve DWI.…”
Section: Discussionmentioning
confidence: 99%
“…Due to an expected increase in patient numbers, optimizing patient comfort and throughput is desirable. Most commonly, conventional echo planar imaging based single‐shot (DW‐EPI SS ) DWI sequences are implemented in multiparametric MRI protocols, which provide reliable image quality, but show a high rate of susceptibility artifacts . At the same time, spatial resolution is limited, with the potential risk of missing subtle findings .…”
mentioning
confidence: 99%
“…More advanced functional MR imaging sequences in a custom multiparametric MR imaging (mpMRI) exam have been shown to significantly improve the performance of MRI in cancer diagnosis [9]. In addition, DWI has become a useful tool for differentiating malignant and benign prostatic tissue due to high contrast resolution and the quantitative apparent diffusion coefficient (ADC) [6], [10]. DWI reflects and measures the diffusion of water molecules within biological tissues due to thermal Brownian motion.…”
Section: Introductionmentioning
confidence: 99%
“…However, we are not aware of a study focusing specifically on the imaging of the prostate and quantification of the distortion effects. One exception is a recent study by Li et al [24] that compared SS- DWI and MS-DWI of the prostate using qualitative assessment of a variety of factors such as distortion and lesion conspicuity, targeting primarily staging workflows of the routine clinical care. In this study we include quantitative assessment of both distortion and targeting error, which are critical for image-guided therapy applications.…”
Section: Introductionmentioning
confidence: 99%